ChemInform Abstract: Rapid Access to New Thiazepinyl and Oxazepinyl Phosphonates Through a Green Pudovik Reaction. Issue 22 (12th May 2016) - Saha, Debasmita; Kaur, Tanpreet; Singh, Neetu; Singh, Udai P.; Sharma, Anuj
Abstract: The microwave‐assisted, catalyst and solvent‐free reaction can be scaled up.